2015
DOI: 10.1097/md.0000000000000708
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Somatic Mutations in Chinese Aldosterone-Producing Adenoma Patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 29 publications
5
28
0
Order By: Relevance
“…ATP, CACNA, CTNNB1 ) is considerably low184345. The current cohort and others from Asia (ranging from 59.5 to 76.8%)1843 reported a higher prevalence of APAs harboring KCNJ5 somatic mutations (52.9% in this cohort).…”
Section: Discussionsupporting
confidence: 43%
“…ATP, CACNA, CTNNB1 ) is considerably low184345. The current cohort and others from Asia (ranging from 59.5 to 76.8%)1843 reported a higher prevalence of APAs harboring KCNJ5 somatic mutations (52.9% in this cohort).…”
Section: Discussionsupporting
confidence: 43%
“…Large multicenter studies have confirmed these findings and have shown that these mutations (G151R and L168R) account for 34%-47% of APAs in people of European ancestry (8)(9)(10) and 60%-77% of people of Asian ancestry (11)(12)(13)(14), with differences likely attributable to differences in disease definition. There is also a striking sex dimorphism in European and some Asian cohorts (8,10,11,15,16); European cohorts consistently show that these mutations account for 50%-60% of women with APAs, but only 20% of men, and KCNJ5 mutations are more prevalent in younger patients (8,10).…”
Section: Introductionsupporting
confidence: 53%
“…One of these (R510X) must result in a truncated non-functional channel. Another APA mutation, V728I, reported previously only once in an APA of a Chinese patient [18,38] is frequently present germline in healthy individuals [39 heterozygous alleles in EXAC database]. This also questions if it alone can account for excessive aldosterone production.…”
Section: Discussionmentioning
confidence: 99%